2013
DOI: 10.1103/physrevc.88.024604
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties and shear viscosity over entropy-density ratio of the nuclear fireball in a quantum-molecular dynamics model

Abstract: Thermodynamic and transport properties of nuclear fireball created in the central region of heavyion collisions below 400 MeV/nucleon are investigated within the isospin-dependent quantum molecular dynamic (IQMD) model. These properties including the density, temperature, chemical potential, entropy density (s) and shear viscosity (η), are calculated by a generalized hot Thomas Fermi formulism and a parameterized function, which was developed by Danielewicz. As the collision goes on, a transient minimal η/s = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…Some authors simply take σ med NN as a fraction, e.g. half, of the free cross section [26][27][28][29]. The deficiency of this assumption is that the free NN cross sections are not recovered when the matter becomes sufficiently dilute.…”
Section: The Nn Cross Section In the Nuclear Mediummentioning
confidence: 99%
“…Some authors simply take σ med NN as a fraction, e.g. half, of the free cross section [26][27][28][29]. The deficiency of this assumption is that the free NN cross sections are not recovered when the matter becomes sufficiently dilute.…”
Section: The Nn Cross Section In the Nuclear Mediummentioning
confidence: 99%
“…In the current work, six source systems with different masses and charge numbers but with similar N/Z of approximately ∼ 1.3, i.e., (A,Z) = (36, 15), (52,24), (80, 33), (100, 45), (112, 50), and (129, 54), are excited at an initial temperature varying from 0 to 20 MeV. The de-excitation process can be studied using the ThIQMD model [25].…”
Section: Calculations and Discussionmentioning
confidence: 99%
“…where ρ is the total density of the nuclear system, which is calculated using the interaction density in IQMD [23,24,48,49] as follows:…”
Section: Modelmentioning
confidence: 99%
“…The quark-gluon plasma (QGP) produced in ultrarelativistic heavy-ion collisions is believed to be a nearly ideal fluid and has a very small specific shear viscosity η/s [1-4], i.e., the ratio of the shear viscosity η to the entropy density s. It has been further found that the η/s decreases with increasing temperature in the hadronic phase while increases with increasing temperature in QGP, resulting in a minimum value at the temperature of hadron-quark phase transition [5,6]. At even lower temperatures, the η/s of nuclear matter with nucleon degree of freedom has been investigated from the relaxation time approach [7-9] and transport model studies [10][11][12][13]. Similar to the behavior near hadron-quark phase transition, the η/s also shows a minimum in the vicinity of nuclear liquid-gas phase transition from various approaches [11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…At even lower temperatures, the η/s of nuclear matter with nucleon degree of freedom has been investigated from the relaxation time approach [7-9] and transport model studies [10][11][12][13]. Similar to the behavior near hadron-quark phase transition, the η/s also shows a minimum in the vicinity of nuclear liquid-gas phase transition from various approaches [11][12][13][14][15][16]. Since the correlation between the elliptic flow and the specific shear viscosity seems to be a general feature in not only relativistic [3] but also intermediate-energy heavy-ion collisions [17], it might be promising to measure the η/s experimentally, meanwhile providing an alternative way of searching for nuclear liquid-gas phase transition in heavy-ion collisions at intermediate energies in the future.…”
mentioning
confidence: 99%